In vitro analysis of the effect of ragweed extract against Monilinia laxa - Tóth, Csaba Tamás; Miskolczi, Panna Márta; Csubák, Mária (Acta Agraria Debreceniensis, 2012)
Nowadays in Hungary nearly 5 million hectares of agricultural area was infected with ragweed (Ambrosia artemisiifolia). According to the public opinion the ragweed is a weed. From agricultural and public health point of view it is exceptionally dangerous plant. As it contains a number of useful active ingredients, based on this the ragweed is consider a medicinal plant. Our goal was to present that the ragweed contains antifungal active substances as well. In the experiments we used the pre-flowering plants with roots and we extracted the biological active components of dried plant. We tested the biological activity of the extracts against Monilinia laxa in vitro. We related based on our examination that ragweed contains biologically active agents, by which it is hampered the reproduction of the Monilinia laxa.